Hip joint biomechanical parameters and their relationship with the esthetic functional performance of the développé à la seconde movement in classical ballet dancers - Metzen, F.; Ribeiro-Alvares, J. B.; Pompeo, K. D.; Sonda, F. C.; Santos, R. S.; Vaz, M. A. (Journal of Applied Biomechanics, 2023)
Développé à la seconde is a classic ballet movement that requires the maintenance of a high hip joint range of motion (ROM) and muscle strength. However, the contribution of these hip joint biomechanical parameters to this movement`s esthetic performance is unclear. Therefore, this study evaluated hip joint biomechanical characteristics of 21 experienced ballet dancers (15-29 y old) and verified the relationship between these variables with the développé à la seconde static and dynamic performance. Correlations between age, ballet practice time, gluteus maximus and gluteus medius thicknesses, ROM, and muscle strength with absolute and relative static and dynamic performances were verified. Flexors, extensors, and internal rotators peak strength and external rotation ROM were highly correlated with absolute and relative static performances (0.5-0.7). Flexors and extensors strength and external and internal rotation ROM showed the highest correlations with the développé dynamic performance (0.49-0.67). Flexor strength and flexor and internal rotation ROM predicted 26% to 41% of this movement`s static and dynamic performances. Thus, from a biomechanical perspective, clinical assessment of hip strength and ROM may be used to predict the quality of the ballet dancers` performance of the développé à la seconde and guide classical ballet training.